Acetylshikonin suppresses diffuse large B-Cell Lymphoma cell growth by targeting the T-lymphokine-activated killer cell-originated protein kinase signalling pathway. Issue 2 (1st February 2022) - Cui, Jieke; Guo, Rong; Wang, Yingjun; Song, Yue; Song, Xuewen; Li, Hongwen; Song, Xiaoqin; Li, Jiwei
ABSTRACT: Diffuse large B-cell lymphoma (DLBCL) is one of the most common causes of cancer death worldwide, and responds poorly to the existing treatments. Thus, identifying novel therapeutic targets of DLBCL is urgently needed. In this study, we found that T-lymphokine-activated killer cell-originated protein kinase (TOPK) was highly expressed in DLBCL cells and tissues. Data from the GEPIA database also indicated that TOPK was highly expressed in DLBCL tissues. The high expression levels of proteins were identified via Western blots and immunohistochemistry (IHC). TOPK knockdown inhibited cell growth and induced apoptosis of DLBCL cells with 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2 H-tetrazolium (MTS) and flow cytometry. Further experiments demonstrated that acetylshikonin, a compound that targeted TOPK, could attenuate cell growth and aggravate cell apoptosis through TOPK/extracellular signal-regulated kinase (ERK)-1/2 signaling, as shown by MTS, flow cytometry and Western blots. In addition, we demonstrated that TOPK modulated the effect of acetylshikonin on cell proliferation and apoptosis in U2932 and OCI-LY8 cells using MTS, flow cytometry and Western blots. Taken together, the present study suggests that acetylshikonin suppresses the growth of DLBCL cells by attenuating TOPK signaling, and the targeted inhibition of TOPK by acetylshikonin may be a promising approach for the treatment of DLBCL. GRAPHICAL ABSTRACT: uf0001